Adaptiveness of dark personalities: psychopathy and sadism have opposite associations with fertility - Međedović, Janko; Hromatko, Ivana (Frontiers in Psychology, 2025)
Analyzing the links between behavioral traits and fertility is a pivotal step toward understanding their current adaptiveness and the potential regimes of natural selection acting upon them. In this study, we examined associations between the Dark Tetrad traits—psychopathy, narcissism, Machiavellianism, and sadism—and two fertility indicators: number of children and age of first reproduction, in a representative probabilistic sample of Croatian citizens (N = 690). Regression analyses showed that psychopathy positively predicted the number of children and negatively predicted age of first reproduction; the opposite pattern was observed for sadism. Mediation analysis further revealed that age of first reproduction mediated the relationship between sadism and number of children, while the mediation effect for psychopathy was marginally significant. These findings add to existing evidence suggesting that psychopathy may confer adaptive advantages in terms of evolutionary fitness, potentially supporting positive directional selection for this trait. In contrast, sadism may be maladaptive in an evolutionary context. Additionally, the results contribute to the ongoing debate regarding the potential redundancy of psychopathy and sadism as behavioral dispositions, indicating that such a conclusion may be premature.